Structural Insight into Catalysis by the Flavin-Dependent NADH Oxidase (Pden_5119) of Paracoccus denitrificans - Kryl, Martin; Sedláček, Vojtěch; Kučera, Igor (International journal of molecular sciences, 2023)
The Pden_5119 protein oxidizes NADH with oxygen under mediation by the bound flavin mononucleotide (FMN) and may be involved in the maintenance of the cellular redox pool. In biochemical characterization, the curve of the pH-rate dependence was bell-shaped with pKa1 = 6.6 and pKa2 = 9.2 at 2 μM FMN while it contained only a descending limb pKa of 9.7 at 50 μM FMN. The enzyme was found to undergo inactivation by reagents reactive with histidine, lysine, tyrosine, and arginine. In the first three cases, FMN exerted a protective effect against the inactivation. X-ray structural analysis coupled with site-directed mutagenesis identified three amino acid residues important to the catalysis. Structural and kinetic data suggest that His-117 plays a role in the binding and positioning of the isoalloxazine ring of FMN, Lys-82 fixes the nicotinamide ring of NADH to support the proS-hydride transfer, and Arg-116 with its positive charge promotes the reaction between dioxygen and reduced flavin.
Keywords: FMN; Oxidation-Reduction; oxidace-redukce; dioxygen reduction; NAD; Flavin Mononucleotide; Kinetics; Catalysis; Paracoccus denitrificans; flavinmononukleotid; flaviny; Flavins; katalýza; kinetika; NADH